Diagnostic Concordance Of High-Resolution Ultrasonography And 1.5-Tesla Magnetic Resonance Imaging In Non-Traumatic Shoulder Pain: A Cross-Sectional Study At A Tertiary Care Hospital. - Pandian, Soundara; Kumar, Pasupuleti Santosh (Journal of Neonatal Surgery, 2025)
Background: Non-traumatic shoulder pain is a highly prevalent musculoskeletal complaint, accounting for 7–26% of all musculoskeletal referrals. High-resolution ultrasonography (HRUS) offers real-time, dynamic, cost-effective assessment of shoulder soft-tissue pathologies, while 1.5-Tesla MRI provides superior characterisation of cartilaginous, labral, and intra-articular structures. This study evaluated the diagnostic concordance of HRUS and MRI in adults with non-traumatic shoulder pain. Methods: A cross-sectional diagnostic-accuracy study included 100 adults (≥18 years) with non-traumatic shoulder pain of >4 weeks’ duration. HRUS (7–14 MHz linear probe) and 1.5-T MRI shoulder were performed within 7 days, with each radiologist blinded to the other modality's results. Sensitivity, specificity, positive and negative predictive values, accuracy, and Cohen's kappa for inter-modality agreement were calculated with MRI as the reference standard. Results: For supraspinatus full-thickness tears: HRUS sensitivity 92.0%, specificity 96.0%, kappa 0.84. Partial-thickness tears: sensitivity 73.0%, specificity 88.0%, kappa 0.62. Biceps tendinopathy: kappa 0.79. Subacromial-subdeltoid bursitis: kappa 0.81. Labral pathology: kappa 0.45. Calcific tendinitis: kappa 0.88. HRUS was limited for deep structures (labarum, glen humeral cartilage, intra-articular bodies). Conclusion: HRUS demonstrated excellent concordance with MRI for full-thickness rotator-cuff tears, bursitis, and calcific tendinitis. Partial-thickness tears and labral pathology showed moderate concordance, underscoring MRI's indispensability for equivocal HRUS findings. HRUS should be the recommended first-line modality for shoulder imaging in tertiary care settings, reserving MRI for HRUS-negative cases with high clinical suspicion or suspected labral/intra-articular pathology